Elaboración del estudio de prefactibilidad para el montaje de Servicio de Gerencia de proyectos en la Empresa WSI Ltda. (2013)
The following document presents the "Preparation of the Pre-Feasibility Study for the Assembly of the Project Management Service in WSI Ltda." For the hydrocarbon sector that is where WSI Ltda. Has experience and on which the different studies focused . However, as a result of the research it is recommended to take into account other sectors that demand the Project Management service. Below is a brief reference to what will be found in each of the studies carried out: Market Studies: Supply and demand studies were carried out for which, at the level of the Offer, the companies that currently provide the Project Management service for the hydrocarbons sector were identified and analyzed. Reviewing in detail the most recognized by their size and experience and demand level, the studies focused on the 10 oil operators with the highest production in the last year and the five most important complementary services companies, as well as the verification of the new multinationals that will arrive in the country through the 2012 round of the ANH, taking into account the projects currently being developed and the future ones, where the competition that exists to provide the service is observed Technical Studies: This study evaluated the macro and micro location of WSI Ltda., In relation to potential clients and revised the plans for the remodeling of the offices recommending the location of the area for the assembly of the Project Office , taking into account what is necessary for its operation. Likewise, the documentary standard and the components to be handled for the start-up of the service are considered. Additionally, the costs calculated for the furniture, equipment and software necessary for the operation are listed. Administrative Studies: In this study the revision of the current organizational structure of WSI Ltda. And the incorporation of the service to it was carried out, for which purpose the identification of the profiles, functions, responsibilities, as well as the assignment of resources, salaries, type of contract and hiring process of the professionals that will become part of the Project Management team. Additionally, an administrative cost calculation was made for the operation of the service. Environmental Studies: Because the assembly of the service does not generate a detriment to the environment and additionally within the policies of WSI Ltda. A series of measures have been implemented to mitigate and perform the waste management and other activities of the works in office; additionally and taking into account that they have the ISO 14001 certification, criteria and parameters were identified that WSI Ltda., must validate and value during the execution of the Environmental Management Plans in the development of the projects, in compliance with the environmental regulations applicable. Financial and Financing Studies: The calculation of the investment of the project was made, taking into account the costs of the pre-feasibility study, the costs and expenses foreseen in the market, technical and administrative studies of the present study and the projected costs of the feasibility study. For this study, two types of contracts to be executed were established (Type 1: Feasibility studies and Type 2: Management of the construction of plants and stations in the hydrocarbon sector); additionally, for the calculation of sales, two scenarios were established: prudent optimist and equilibrium point, with which sales (income) and costs and expenses in the execution of contracts can be foreseen. With this information, the approach for the three defined sales alternatives was made and the cash flow of the project for each was obtained, obtaining some conclusions, findings and recommendations. Financial Evaluation: Of the three alternatives proposed in the financial and financing study, the one that was considered the closest to the reality of the sales to be obtained and based on the cash flow of the selected alternative was selected, the IRR and the NPV were calculated. (which were the criteria established for the financial evaluation) in different situations; performing a sensitivity analysis that allows observing the limits that can be reached in the development of the project without it ceasing to be profitable.